2013
DOI: 10.1021/jm400125h
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Replication Inhibitors That Target the Viral NS4B Protein

Abstract: We describe the preclinical development and in vivo efficacy of a novel chemical series that inhibits hepatitis C virus replication via direct interaction with the viral nonstructural protein 4B (NS4B). Significant potency improvements were realized through isosteric modifications to our initial lead 1a. The temptation to improve antiviral activity while compromising physicochemical properties was tempered by the judicial use of ligand efficiency indices during lead optimization. In this manner, compound 1a wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 71 publications
2
45
0
Order By: Relevance
“…We therefore used a humanized-mouse model to determine the efficacy of GSK8853 as monotherapy to treat HCV infection with a genotype 1a PBC002 virus strain. Abbreviated results from this study along with data on the synthesis of prodrug GSK9574 have been previously reported (6), and this current work significantly expands on the previously reported data and analysis. Prior to compound testing performed with the in vivo infection model, the NS4B sequence from PBC002 was used to construct a chimeric replicon to ensure that the potency of GSK8853 against this strain was similar to that of our standard in vitro replicons.…”
Section: Gsk8853 Inhibits Multiple Hcv Genotypes and Generates Resistsupporting
confidence: 76%
See 2 more Smart Citations
“…We therefore used a humanized-mouse model to determine the efficacy of GSK8853 as monotherapy to treat HCV infection with a genotype 1a PBC002 virus strain. Abbreviated results from this study along with data on the synthesis of prodrug GSK9574 have been previously reported (6), and this current work significantly expands on the previously reported data and analysis. Prior to compound testing performed with the in vivo infection model, the NS4B sequence from PBC002 was used to construct a chimeric replicon to ensure that the potency of GSK8853 against this strain was similar to that of our standard in vitro replicons.…”
Section: Gsk8853 Inhibits Multiple Hcv Genotypes and Generates Resistsupporting
confidence: 76%
“…The previously described preclinical drug metabolism and pharmacokinetics (DMPK) data for GSK8853 (7) suggested that an efficacious dose would not be easily attainable, so a phosphate prodrug form of this compound with improved DMPK properties, GSK9574 (Fig. 1B), was selected for use (6). A pilot PK study of GSK9574 in PXB mice determined that oral BID dosing at 10, 30, or 100 mg/kg would deliver levels of GSK8853 expected to be efficacious (see Fig.…”
Section: Gsk8853 Inhibits Multiple Hcv Genotypes and Generates Resistmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Since its introduction, MFSDA has been used as a convenient source of 'CuCF 3 ' and has proved useful in the trifluoromethylation of subpophyrins, 27 pyrazoles, 28 purine nucleosides, 29,30 oxazolyl intermediates, 31 pyrazolopyridines, 32 and others. 33,34 The accepted mechanism comprises an initial step involving the formation of a copper salt with the elimination of methyl halide.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Other classes of DAAs showing clinical efficacy target the NS5A protein (3,4) or viral polymerase (NS5B; reviewed in reference 5). Of the other viral proteins, several smallmolecule DAAs to nonstructural protein NS4B have been identified (6)(7)(8)(9)(10)(11)(12)(13)(14), but to date, there are no examples of clinically active NS4B-targeting compounds.…”
mentioning
confidence: 99%